Protection from Oxidative Stress–Induced Apoptosis in Cortical Neuronal Cultures by Iron Chelators Is Associated with Enhanced DNA Binding of Hypoxia-Inducible Factor-1 and ATF-1/CREB and Increased Expression of Glycolytic Enzymes, p21(waf1/cip1), and Erythropoietin - Zaman, Khalequz (J Neurosci, 1999)
Iron chelators are pluripotent neuronal antiapoptotic agents that have been shown to enhance metabolic recovery in cerebral ischemia models. The precise mechanism(s) by which these agents exert their effects remains unclear. Recent studies have demonstrated that iron chelators activate a hypoxia signal transduction pathway in non-neuronal cells that culminates in the stabilization of the transcriptional activator hypoxia-inducible factor-1 (HIF-1) and increased expression of gene products that mediate hypoxic adaptation. We examined the hypothesis that iron chelators prevent oxidative stress–induced death in cortical neuronal cultures by inducing expression of HIF-1 and its target genes. We report that the structurally distinct iron chelators deferoxamine mesylate and mimosine prevent apoptosis induced by glutathione depletion and oxidative stress in embryonic cortical neuronal cultures. The protective effects of iron chelators are correlated with their ability to enhance DNA binding of HIF-1 and activating transcription factor 1(ATF-1)/cAMP response element–binding protein (CREB) to the hypoxia response element in cortical cultures and the H19-7 hippocampal neuronal cell line. We show that mRNA, protein, and/or activity levels for genes whose expression is known to be regulated by HIF-1, including glycolytic enzymes, p21(waf1/cip1), and erythropoietin, are increased in cortical neuronal cultures in response to iron chelator treatment. Finally, we demonstrate that cobalt chloride, which also activates HIF-1 and ATF-1/CREB in cortical cultures, also prevents oxidative stress–induced death in these cells. Altogether, these results suggest that iron chelators exert their neuroprotective effects, in part, by activating a signal transduction pathway leading to increased expression of genes known to compensate for hypoxic or oxidative stress.